Enforcing Alternative Justice Administration in a Higher Education lnstitution - Pichayapaiboon, Suwimol (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research of "Enforcing Alternative Justice Administration in Higher Education Institution" was to investigate the general condition of a criminal offense against the person, liberty, defamation, crime against property and petty offense and to investigate criminal offenses affecting the alternative justice administration system. This was a quantitative and qualitative research. The targeted population for the quantitative research was higher education students and lecturers using a questionnaire as an instrument for data collection. The sample size was based on Yamane’s. Data analyses were mean, standard deviation, skewness and kurtosis of the empirical data with the structural model by applying the PLS-Graph program. The results revealed that all groups were moderately to highly knowledgeable about the process of choice. Choices include crimes, such as offenses against the person, guilty of burglary over time, guilty of theft of equipment, or armed burglary, guilty of theft by means of the acquisition of the property, offences relating to loss of property and petty offenses. They have a direct influence on the process, so the choice of such a criminal offense should provide enabling legislation to implement the alternative justice administration process.